Application of Design Thinking in the Development of the Beres.in Application: an Integrated Solution for Moving and Home Cleaning Services - Ainiyya Hana Pathi Seruni; Yulia Suryadi; Gindu Siswo (Eduvest - Journal of Universal Studies, 2026)
The increase in mobility of urban residents, especially in Bogor City, has created a new need for moving and home cleaning services that are efficient, transparent, and easily accessible digitally. Changes in the lifestyle of urban communities that demand convenience and practicality encourage the need for integrated solutions that address the challenges of time efficiency and trust in service providers. This research aims to develop the concept and design of the "Beres.in" application as an integrated home cleaning and moving service platform using a design thinking approach. The research is carried out through four stages, namely empathize, define, ideate, and prototype, in order to understand user needs in depth and test to explore user needs and formulate empathy-based solutions. The results of the study show that potential users are dominated by Generation Z women and millennials who have a high level of digital activity and prioritize time efficiency. The main problems found include price uncertainty, lack of trust in workers, and limited schedule flexibility. Based on these findings, an application prototype was developed with automatic price estimation features, verified worker profiles, a real-time booking system, and direct communication channels to increase user trust and comfort. This research has original value in integrating two different services into one digital ecosystem based on user-centered design, and proves that the application of design thinking is effective in producing service innovations that are adaptive to the needs of modern urban society.